Penggunaan GenAI terhadap Kemampuan Berpikir Kritis Mahasiswa PGSD - Petrus Murwanto; Ria Triayomi (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The presence of Generative Artificial Intelligence (GenAI) in the field of education introduces new dynamics in the learning process, particularly in relation to the development of students' critical thinking skills. This study aims to explore students' perceptions of GenAI usage and its impact on their critical thinking abilities. A descriptive quantitative approach was employed, involving 101 students from the Primary School Teacher Education (PGSD) Program at Universitas Katolik Musi Charitas. Data were collected through an online questionnaire covering various aspects of critical thinking and students’ interactions with GenAI. The findings reveal that most students (47,52 %) perceive GenAI as a moderately helpful tool in supporting critical thinking; however, they are 70, 3 % also aware of its potential to reduce critical thinking quality when used without reflection or verification. While a positive trend is observed (56 %) in the practice of cross-checking information, challenges remain, including low information literacy and lack of knowledge regarding credible sources (56,4 %), insufficient procedural understanding (38,5%) and limited time (30,8). Therefore, the integration of GenAI in educational contexts must be supported by pedagogical strategies that promote digital literacy and strengthen students' critical thinking skills to ensure that technology is utilized optimally and responsibly in academic settings.